Counteracting store brand introduction by the strategic incorporating of fairness concern behavior. Issue 2 (26th June 2021) - Huang, Lingchen; Feng, Ting; Huang, Zongsheng
Abstract : Purpose: Responding to the store brand (SB) introduction by the retailer, the manufacturer may adopt the strategic choice of incorporating the fairness concern behavior of the retailer. This paper aims to examine how the manufacturer can counteract the retailer's SB introduction by strategically choosing to or not to incorporating the retailer's fairness concern. Design/methodology/approach: This paper considers the SB introduction problem in a two-echelon supply chain consisting of one manufacturer and one retailer with fairness concern behavior. This paper resolves the pricing strategies under four strategic scenarios regarding fairness concern incorporation and SB introduction and examine the influences from the fairness concern on pricing strategies and profits. This paper further investigates the strategic choice equilibrium of the manufacturer and retailer on fairness concern and SB introduction decision. Findings: The results show that the retailer can be better off by the introduction of the SB only when the acceptance degree of the SB is high enough. And whether the manufacturer should incorporate the retailer's fairness concern depends on the consumer's acceptance of the SB: Only when the consumer's acceptance is moderate, the manufacturer is able to counteract the SB by strategically not incorporating the retailer's fairness concern behavior. Otherwise, the manufacturer cannot prevent the retailer from introducing the SB and can be better off by incorporating the retailer's fairness concern behavior. Originality/value: This paper contributes to the literature by examining whether the manufacturer can adopt the strategic incorporation of the retailer's fairness concern to counteract the retailer's SB introduction.